Performance Assessment Analysis of Forest Management Unit of Region I Stabat. North Sumatera Province - OK Hasnanda Syahputra; saleh, rinaldy (Talenta Publisher, 2022)
The Forest Management Unit (FMU/KPH) Region I Stabat, Langkat Regency, North Sumatra Province has an important role in realizing success and forest management at the site level. The description of the performance of FMU development is required by policy makers as part of the policy evaluation. In the evaluation of the policy, an assessment of the substance, implementation, and impact of the policy can be carried out. Policy evaluation is functional, with the intention of providing input for process improvement and continuous improvement of performance measures. However, there are still problems in the field that must be addressed immediately so that forest resource management can run well, such as the unfinished process of boundary demarcation reconstruction, regional stability, investment mechanisms and so on. The purpose of this research is to assess the performance of the successful level of forest management implementation at the site level. The method used in the assessment is the analysis of the components of the criteria and indicators developed by Forest Watch Indonesia (FWI) Version 2.0, document verification, and in-depth interviews. The results of the assessment show that the FMU Region I Stabat has a fairly good performance in carrying out forest management in accordance with its function as a forest resource manager at the site level. Several criteria need to be strengthened so that these criteria can run well. These criteria include regional stability and investment mechanisms.